A practical beginner's guide to Raman microscopy. Issue 6 (16th June 2021) - Zapata, Félix; López-Fernández, Adrián; Ortega-Ojeda, Fernando; Montalvo, Gemma; García-Ruiz, Carmen
Abstract: Raman microscopy is a highly suitable and well settled down analytical technique for qualitative determination of chemical substances. However, many university undergraduate chemical degrees do not incorporate its practical training in the experimental laboratory practises that constitute their curricula. For this reason, this work aimed at designing a practical beginner's guide to Raman microscopy useful for undergraduate students, teachers or practitioners who need to use it for the first time. After a brief explanation of the main concepts about Raman microscopy, the methodology development and results interpretation are mainly explained using paracetamol (acetaminophen) drugs as example. In addition, this guide presents an application to the identification of different components within a mixture, which shows the instrumental potential and how to use it effectively. Finally, acetaminophen, ascorbic acid, and sucrose were positively detected using Raman microscopy on a commercial drug whose major component was acetaminophen. In fact, the guide shows the detection and unequivocal identification of different components in the mixtures, even for those low concentration components (5-10% mass ratio). This work clearly proposes different pragmatic criteria at the laboratory for identifying substances in mixtures to promote an easy implementation of the Raman microscopy technique. Graphical Abstract: UF0001